Implementation and survey evaluation of a new safety concern escalation pathway among nursing team members - Indica Sur; Rocel D. Besa; Stephanie Ceylan; Brett Sealove; Elliot Frank (PLoS ONE, 2025)
Introduction Escalating patient safety concerns is a critical component of healthcare delivery and can be impeded by organizational barriers including power hierarchies and fear of retaliation. Nursing team members are pivotal in identifying and addressing real-time safety issues. The existing literature on increasing “speaking-up” behaviors among nursing team members predominantly focuses on communication training rather than simplifying the escalation process. The current project aimed to evaluate the awareness and perceptions of a newly implemented pathway to streamline concern escalation among nursing team members at a tertiary academic medical center. Although the pathway was embraced and regularly utilized by nursing supervisors, we sought to determine whether front-line staff were aware of, and confident in, the use of the pathway. Methods A new escalation pathway for communicating concerns was developed and implemented in response to a patient safety event and subsequent root cause analysis. An investigator-developed electronic survey was distributed to nursing team members and assessed (1) demographic data, (2) experiences with escalating safety concerns, and (3) awareness, use, and attitudes toward the new pathway. Recruitment and data collection occurred in two stages, and responses were collected via REDCap. Data were analyzed using descriptive statistics and qualitative thematic analysis of free-text response items. Results 128 of 129 total responses were analyzed. Of 89 (69.5%) participants who indicated they had ever encountered a situation requiring escalation, 48 of them (53.9%; 37.5% of all respondents) reported hesitating to act because they were uncertain how to escalate the concern. 25.6% of respondents had already used the new pathway for escalating concerns, and 79% thought they would use the pathway in the future. However, 41% expressed ambivalence about its impact on their confidence in escalating concerns and 47% were still unsure how to use the matrix/pathway. Thematic analysis of 51 free-text response items identified five key themes which provided useful provided useful insights to guide ongoing education and support for the escalation process. Conclusion The new escalation pathway was positively received and improved confidence for many, though some gaps in awareness and training persist.